FDG-PET is prognostic and predictive for progression-free survival in relapsed follicular lymphoma: exploratory analysis of the GAUSS study. Issue 2 (1st February 2017) - Kostakoglu, Lale; Goy, Andre; Martinelli, Giovanni; Caballero, Dolores; Crump, Michael; Gaidano, Gianluca; Baetz, Tara; Buckstein, Rena; Fine, Gregg; Fingerle-Rowson, Guenter; Berge, Claude; Sahin, Deniz; et al.
Abstract: An exploratory analysis of 75 follicular lymphoma patients treated with obinutuzumab or rituximab induction therapy (IT) for 4 weeks in the phase II GAUSS study aimed to determine whether positron emission tomography (PET) results could predict progression-free survival (PFS) and tumor response. The proportion of patients with a PFS event (progression or death) was higher in those who were PET-positive after IT (assessed using Deauville five-point scale criteria; 35/52, 67%) than PET-negative (5/20, 25%); the hazard ratio for progression or death was 0.25 (95%CI: 0.01–0.64; p  = 0.0018). A significant association was also found when PET results were assessed using International Harmonization Project and European Organisation for Research and Treatment of Cancer criteria. Change between baseline and end of IT in values of standardized uptake value and other PET parameters were associated with PFS and response. Validation of these results in prospective studies of larger cohorts is warranted.